Empirical targets for acute hemodynamic management of individuals with spinal cord injury. (17th September 2019) - Squair, Jordan W.; Bélanger, Lise M.; Tsang, Angela; Ritchie, Leanna; Mac-Thiong, Jean-Marc; Parent, Stefan; Christie, Sean; Bailey, Christopher; Dhall, Sanjay; Charest-Morin, Raphaele; Street, John; Ailon, Tamir; et al.
Abstract : Objective: To determine the hemodynamic conditions associated with optimal neurologic improvement in individuals with acute traumatic spinal cord injury (SCI) who had lumbar intrathecal catheters placed to measure CSF pressure (CSFP). Methods: Ninety-two individuals with acute SCI were enrolled in this multicenter prospective observational clinical trial. We monitored mean arterial pressure (MAP) and CSFP during the first week after injury and assessed neurologic function at baseline and 6 months after injury. We used relative risk iterations to determine transition points at which the likelihood of either improving neurologically or remaining unchanged neurologically was equivalent. These transition points guided our analyses in which we examined the linear relationships between time spent within target hemodynamic ranges (i.e., clinical adherence) and neurologic recovery. Results: Relative risk transition points for CSFP, MAP, and spinal cord perfusion pressure (SCPP) were linearly associated with neurologic improvement and directed the identification of key hemodynamic target ranges. Clinical adherence to the target ranges was positively and linearly related to improved neurologic outcomes. Adherence to SCPP targets, not MAP targets, was the best indicator of improved neurologic recovery, which occurred with SCPP targets of 60 to 65 mm Hg. Failing to maintain the SCPP within the target ranges was an important detrimental factor in neurologic recovery, particularly if the target range is set lower. Conclusion: We provide an empirical, data-driven approach to aid institutions in setting hemodynamic management targets that accept the real-life challenges of adherence to specific targets. Our results provide a framework to guide the development of widespread institutional management guidelines for acute traumatic SCI.